Reservoir characteristics of the Kuhlan sandstones from Habban oilfield in the Sabatayn Basin, Yemen and their relevance to reservoir rock quality and petroleum accumulation - Al-hasani, A. (Elsevier Ltd, 2018)
Integrated petrophysical and petrographic analyses were performed on the Kuhlan clastic rocks to evaluate the petrophysical reservoir properties, identify grain sorting along with the clay type and mineral volumes using well logs coupled with core data. Core samples were collected from two key wells and their results were used to determine the reservoir properties and bulk mineralogical composition and, additionally, to calibrate the well log results from three un-cored to the two cored wells. The Kuhlan clastic reservoir rocks have porosity values between 6 and 12. These porosity values are mainly intergranular primary and secondary porosity. Permeability is likewise variable with values in the range of 78â304 mD. The Kuhlan reservoir rocks also have high hydrocarbon saturation exceeding 70, with relatively high movable oil. These reservoir properties are achieved from log-derived and core porosity and permeability results. The lithology and mineral composition of the well logs and petrographic studies in this study indicate that the Kuhlan sandstone can be considered as an alternative reservoir rock in the basin. The Kuhlan Formation is primarily composed of sandstone that contains quartz, feldspar (i.e., orthoclase, plagioclase (albite) minerals and illite, and calcite cements. The quartz mineral is dominant followed by feldspar as the second most abundant mineral in this formation. The Kuhlan Formation sandstones are classified (based on standard rock classification schemes) into arkose, sub-arkose and feldspathic lithofacies. The results of petrographic analysis also indicate a continental block transitional source of the Kuhlan Formation sandstones. Petrographically, the Kuhlan sandstones are poorly sorted and range from fine to coarse-grained and contain high percentages of detrital quartz and feldspar-rich grains with a significant amount of rock fragments. The Kuhlan sandstones also contain a variable range of matrix and cement contents. Based on the results of this study, the reservoir quality of the Kuhlan sandstone ranges between good to poor reservoir quality. The Kuhlan Formation has arkosic and sub-arkosic sandstones that result in a good reservoir quality with a significant increase of the permeability and intergranular porosity. This is attributed to the coarse-grained texture, high percentages of detrital quartz, slightly well sorted texture and the low degree of matrix and cements. In contrast, the Kuhlan Formation feldspathic sandstone has poor reservoir quality due to the poor sorting texture, pore space occluding clayey groundmass, and carbonate cement. Â© 2018 Elsevier Ltd